FAKTOR-FAKTOR YANG MEMPENGARUHI PELAKSANAAN KEBIJAKAN AKSES TERBUKA REPOSITORI DIGITAL SEBAGAI UPAYA KETERBUKAAN INFORMASI DALAM EKOSISTEM DIGITAL PERPUSTAKAAN PERGURUAN TINGGI NEGERI SE JAWATENGAH - Eko Handoyo; Atin Istiarni (Perpustakaan Nasional RI, 2020)
The aim of the study is viewing the policy making, related to supporting ofthe existence of digital ecosystems in the use of repositories while protecting intellectual property rights. The sample taken was State University Library (PTN) in Central Java. The research method used is descriptive qualitative. Retrieval of the data was taken by questionnaires that distributed to all PTN libraries in Central Java and study documents that support the research. Results of the study indicate that all PTN libraries in Central Java have used a repository. Meanwhile the average software that used by the librarywere E-prints, with the rest of its using Slims (Senayan Library Information Management System) and a software that they make their own for library applications. The contentsin the repository are scientific academic papers such as Final Project Report(TA), Thesis, dissertation, journals, and scientific magazines. The access policy applied by the informant wereopen access, partial and close access policy. The legal formalthatused in implementing the repository access policy at the institutions is by issuing a Rector's Decree (SK), Standard Operating Procedure (SOP), and university policies. While the head library role’s in implementing the repository is become a facilitator in compilingthe legal formal and repository content access policy.